The influence of synthetic pyrethroids on phytophagous mites and their natural enemies in apple orchards - Heunis, J. M. (Juanita Maria) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 1992.